If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2x + -4) + 5(3x + 6) = 29 Reorder the terms: 8(-4 + 2x) + 5(3x + 6) = 29 (-4 * 8 + 2x * 8) + 5(3x + 6) = 29 (-32 + 16x) + 5(3x + 6) = 29 Reorder the terms: -32 + 16x + 5(6 + 3x) = 29 -32 + 16x + (6 * 5 + 3x * 5) = 29 -32 + 16x + (30 + 15x) = 29 Reorder the terms: -32 + 30 + 16x + 15x = 29 Combine like terms: -32 + 30 = -2 -2 + 16x + 15x = 29 Combine like terms: 16x + 15x = 31x -2 + 31x = 29 Solving -2 + 31x = 29 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 31x = 29 + 2 Combine like terms: -2 + 2 = 0 0 + 31x = 29 + 2 31x = 29 + 2 Combine like terms: 29 + 2 = 31 31x = 31 Divide each side by '31'. x = 1 Simplifying x = 1
| (2x+28)(4x+10)= | | -3x+1=-2(3x+10) | | 2w^2+2w=34 | | 5r+15=2.25r | | 3(6+x)=30 | | 3x+4-2-x=14 | | -3(e+4)=4w-5 | | -3+2x=-x-6 | | 1-6x=5-4x | | 22-44= | | 13x+9=-15 | | 2a+4.2=3a-16 | | 2y+4=26 | | XY=98 | | 12p=-4 | | -6n+7n+4= | | 5k+8(k-4)=-84 | | 4x-7=x-34 | | 5y-5=7y+9+10y+4 | | -11=1+8k | | k*(-9k)*k=0 | | X(3x-5)=(3x+8)(x-5) | | 3+2(3n+2)=41 | | 11x+13(19-x)=211 | | -9t(t-2)=4(t-15) | | 2y+120=180 | | 4b=120-5t | | 2b+5=b+10 | | 52=(3x+2) | | 3(x+3)+x=2(x+3)-5 | | 9x^2+27x=7 | | y=3x^2-7x-1 |